Peroxisomal biogenesis disorders in Zellweger syndrome spectrum: diagnosis, monitoring and treatment according to the recommendations of the Global Foundation for Peroxisomal Disorders - M.A. Gonchar; G.R. Muratov; O.L. Logvinova; E.M. Pushkar; E.P. Pomazunovskaya; E.V. Omelchenko; N.V. Shulga; I.M. Galdina; A.S. Zubko; N.V. Strebul (Zaslavsky O.Yu., 2018)
The article deals with the modern principles for the diagnosis and treatment of peroxisomal biogenesis disorders of Zellweger syndrome spectrum according to the recommendations of the Global Foundation for Peroxisomal Disorders 2016. The authors presented the clinical features of these diseases. The lesions of the nervous, bone, urinary, endocrine, sensory systems and tooth enamel are characteristic signs of the disease. Our own clinical observation on the disturbances of oxidation of very long chain fatty acids in an infant is considered separately. Section of Zellweger spectrum disorders diagnosis is based on world standards for disease diagnosis and includes markers of very long-chain fatty acid β-oxidation, as well as α-oxidation by pristanic and phytanic acids, metabolism of pipecolic acid and other peroxisomal dysfunctions. The final diagnosis of peroxisomal biogenesis disorders in Zellweger syndrome spectrum at the present stage is established by the genetic testing method, using the sequencing techniques of the new generation for the PEX genes. The severity of neurological disorders and the progressive course of the disease, as well as emergence of the possibility of treating X-linked adrenoleukodystrophy opened the prospects of screening for X-linked adrenoleukodystrophy based on a combination of liquid chromatography and tandem mass spectrometry to detect the elevated levels of very long-chain fatty acids in newborns in blood spots. Clinical monitoring since diagnosis was established includes correction of initial disturbances and revealing disease symptoms, which appear later.